Diagnosis of the socio-economic profile fish farmer coastal region of Pará - Tenório, Geilson Silva; Tenório, Julita Jaciara de Araújo Silva; Campos, Osvaldo Teixeira Lopes; Alves, Jackson Amoras; da Silva, Maria do Rosário Costa; da Silva, Luiz Antônio Fernandes (Seven Editora, 2023)
The state of Pará is presented as the 2nd in the production of fish from fishing, but the production of aquaculture origin lies in 21 th positions in the national ranking, representing only 12.8% of regional production. The decrease in the quantity and size of fish caught favors the increase in price and the number of people interested in aquaculture. Considering the lack of information on aquaculture, specifically in the Pará region Salgado, the objective of the study was to outline a socioeconomic profile of the fish farmer, to identify the main motivations for joining the activity, only the income from aquaculture and finally, the weekly fish consumption. DOI: https://doi.org/10.56238/devopinterscie-016